Dramatization as a teaching-learning strategy in the area of social sciences and its impact on the education of elementary and middle school students (UNIHumanitas, 2019)
This research aimed to determine the level of incidence of dramatization as a teaching-learning strategy in the area of ​​Social Sciences. It was applied to students of Basic School Education and Secondary Education. It is a mixed approach (qualitative-quantitative) adopting the Comparative and experimental levels. The research technique was observation and survey. Formative assessments were applied in two institutions to compare the level of learning with the results of the grades and surveys were carried out to the teacher and students to recognize their incidence, the type of evaluation instrument used and the suggestions of the students and teachers. With the results, it was possible to determine that in Secondary Education where dramatization was applied, better results were obtained compared to the school where the method was not applied. According to the surveys, in general terms, they maintain that dramatization influenced the cognitive, physical, emotional and social development of students, in which several psychomotor and socio-affective skills were stimulated. In a more concrete analysis, dramatization can be considered an integrative model of human development (cognitive, physical, emotional and social) that encompasses the three didactic moments (beginning-development-closure) and adjusting to both conceptual, procedural and attitudinal contents, allowing an evaluation of all areas of human development and breaking the paradigm of competitiveness in education through cooperation. When the data obtained are compared, it allows the understanding that manifests the degree of incidence of dramatization in learning and in the integral development of the human being.
Keywords: dramatization; integral development; social and personal learning